Development of stabilized fuzapladib solution for injection: forced degradation study and pharmacokinetic evaluation. (28th May 2022) - Sato, Hideyuki; Yamane, Chika; Higuchi, Koji; Shindo, Takeshi; Shikama, Hiroshi; Yamada, Kohei; Onoue, Satomi
Abstract: The aim of the present study was to develop and evaluate stabilized injection solutions of fuzapladib sodium hydrate using antioxidants as the stabilizers. To estimate the possible degradation factors and pathways of fuzapladib, forced degradation studies were conducted under thermal, acid, base, oxidative, and light conditions. To select an optimal excipient to stabilize fuzapladib under a solution state, a screening study of antioxidants was carried out to evaluate their effects to inhibit the degradation. The influence of the selected stabilizers on its pharmacokinetic behavior was evaluated in rats after intravenous administration. On the basis of data from the forced degradation study, thermal and oxidative stresses were significant factors accelerating the degradation of fuzapladib. Among eight tested antioxidants, vitamin C (VC) was the most effective stabilizer to suppress the accelerated degradation by heating, as evidenced by 45% inhibition of the degradation. The stabilization effect was enhanced depending on the concentration of VC. After the intravenous administration of fuzapladib (0.5 mg/kg) with or without VC (2.1 mg/kg), there were no significant differences between the pharmacokinetic behaviors of each group. From these findings, VC might be a promising excipient to stabilize the injection solution of fuzapladib without significant influence on its pharmacokinetic behavior.